Produção e qualidade do leite e da carne de caprinos anglo nubianos suplementados com óleos vegetais - Chávari, Andréia Cristina Toniolo [UNESP] (2015)
The main focus of animal food products market has been toward products with lower fat content and fatty acid profile that characterizes them as functional foods. Therefore, this study aimed to evaluate the inclusion of three sources of vegetable oil in lactating goats diet on production in 120 days of lactation, and the effect of these sources and lactation stage on fortnightly composition and fatty acid profile of goat milk at 20, 50, 80 and 110 days of lactation. It was adopted a completely randomized design and there were used 32 Anglo Nubian goats distributed in four treatments: control diet and diets with inclusion of 30 g/kg of dry matter of diet of canola, sunflower or soybean oil. The dairy production was 182,75 kg and there was no difference for treatments. Among the constituents only urea nitrogen was influenced by treatment and presented lower content for control treatment. Lactose content reduced 0,0107g/ day of lactation. Defatted dry extract and somatic cell count had quadratic effect with minimum values around 100 and 33 days of lactation, respectively. The content of urea nitrogen, also with a quadratic effect, was higher at 93 days of lactation. For protein, there was interaction among treatments and period and, at the end of lactation, its content was increased. The inclusion of vegetable oils promoted reduction in total saturated fatty acids (SFA) and increased the total content of monounsaturated fatty acids (MUFA) and conjugated linoleic acid (CLA). The proportions MUFA/SFA, PUFA/SFA and the atherogenicity and thrombogenicity indexes (AI, TI) and the relation HH (hypocholesterolemic fatty acids/ hypercholesterolemic fatty acids) improved with oil addition in animal diets. The addition of vegetable oil in diets for lactating goats improve the fatty acid profile with no impairment on milk production and composition and the milk from early stages of lactation has better nutritional quality